2018
DOI: 10.1017/s0007114517003646
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal vitamin D status and offspring’s growth, adiposity and metabolic health: a systematic review and meta-analysis

Abstract: In this systematic review and meta-analysis of observational studies, we aimed to estimate the associations between prenatal vitamin D status and offspring growth, adiposity and metabolic health. We searched the literature in human studies on prenatal vitamin D status and offspring growth in PubMed, up to July 2017. Studies were selected according to their methodological quality and outcomes of interest (anthropometry, fat mass and diabetes in offspring). The inverse variance method was used to calculate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 63 publications
0
36
0
3
Order By: Relevance
“…It is also possible that VD has an impact on cognitive function throughout the lifespan with a critical window for VD deficiency during pregnancy and early childhood, and only after a long latency period does its impact become more apparent at older ages when cognitive function starts to decline. This goes with the developmental origin of health and disease (DOHaD) paradigm and is supported by studies that showed the link between VD deficiency during pregnancy and various outcomes during childhood or adulthood [ 48 ]. Evidence from animal studies suggest that maternal VD during pregnancy plays a role in the brain development of offspring; however, the association between low maternal VD levels during pregnancy with poor cognition of offspring in humans is inconclusive [ 49 ].…”
Section: Discussionmentioning
confidence: 85%
“…It is also possible that VD has an impact on cognitive function throughout the lifespan with a critical window for VD deficiency during pregnancy and early childhood, and only after a long latency period does its impact become more apparent at older ages when cognitive function starts to decline. This goes with the developmental origin of health and disease (DOHaD) paradigm and is supported by studies that showed the link between VD deficiency during pregnancy and various outcomes during childhood or adulthood [ 48 ]. Evidence from animal studies suggest that maternal VD during pregnancy plays a role in the brain development of offspring; however, the association between low maternal VD levels during pregnancy with poor cognition of offspring in humans is inconclusive [ 49 ].…”
Section: Discussionmentioning
confidence: 85%
“…All these effects indicate how important vitamin D is during gestation [50]. Several observational studies show a relationship between inadequate serum 25(OH)D in pregnant women and adverse neonatal and pregnancy outcomes including preeclampsia, small for gestational age (SGA), preterm birth and gestational diabetes mellitus [51].…”
Section: Vitamin Dmentioning
confidence: 99%
“…Currently, there is no universal definition of vitamin D deficiency [51], and the standards for which adequacy levels were established only considered the levels necessary to maintain bone health [12]. In pregnant women, deficiency prevalence (<50 nmol/L) is estimated to be between 40%-60% in the U.S. [113,114], and as high as 54% globally [115].…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Society of Endocrinology, however, defined deficiency as being lev-els of 25 (OH) D <50 nmol/L (20 ng/mL), insufficiency as between 52.5 and 72.5 nmol/L (21-29 ng/mL) and optimal or adequate levels as >75 nmol/L (>30 ng/mL) (Holick et al, 2011). Regardless of the proposed cut-off points, it has been observed that vitamin D levels <50 nmol/L during pregnancy are associated with an increased risk of preeclampsia (Wei et al, 2013), gestational diabetes (Wei et al, 2013), being small for gestational age (Santamaria et al, 2018;Wei et al, 2013) and preterm infants (Qin, Lu, Yang, Xu, & Luo, 2016;Wei et al, 2013), while levels of 25 (OH) D <30 nmol/L are associated with low birthweight (Santamaria et al, 2018).…”
Section: Vitamin D Status During Pregnancymentioning
confidence: 99%